Microstructural and physical properties of samarium orthoferrite thin films by the sol-gel method - Baqiah, Hussein; Awang Kechik, Mohd Mustafa; Mohammed Al-Hada, Naif; Liu, Jian; Xu, Shicai; Zhang, Na; Li, Qiang; Wang, Zhenxing; Al-Gaashani, Rashad; Wang, Jihua (Elsevier, 2022)
Samarium orthoferrite, SmFeO3 (SFO), is a multifunctional material with promised applications. In this paper, SFO thin films were prepared by sol–gel method onto a quartz substrate at different annealing temperatures (T = 700, 750, 800 and 850 °C) and onto LaNiO3 (LNO) buffered quartz substrate using T = 800 °C. The phase formation, microstructure, electronic, optical, magnetic and ferroelectric properties of the films were investigated and compared. Minimal annealing temperature (T) from thermogravimetric analysis was about 720 °C. From X-ray diffraction analysis, film T = 700 °C showed mixed phases of SFO and a trace amount of Sm2O3 while single phase of SFO was observed for films T = 750 – 850 °C. The lattice parameter c and microstrain reduced for films T = 700 – 800 °C and then increased for film T = 850 °C. From Atomic force microscopy analysis, the porosity, root mean square roughness and particle size of the films increased with the rise of T. All films exhibited high optical transmittance (∼79 – 95 %) in 800 – 550 nm wavelength range and showed two main optical absorptions peaks at about 285 and 385 nm. At lower energy transition, the band gap (Eg) reduced from ∼ 2.79 to 2.72 eV for films T = 700 – 800 °C and then increased to ∼ 2.79 eV for film T = 850 °C. The film’s magnetisation (Ms) tended to increase with T increment. The SFO/LNO film showed higher Ms and Eg than film T = 800 °C.